THE EFFECTS OF AL FATAH PONDOK PESANTREN (SPECIAL FOR TRANSGENDERPEOPLE) ON THEIR RELIGIOUS BEHAVIOURS IN YOGYAKARTA - Wulan Sari, Putri; Ratna Putra, Wahyu; Mitayani, Nur Astri (Pelita - Jurnal Penelitian Mahasiswa UNY, 2013)
The aims of the research were to describe the religious behaviors of the transgenderpeople in Yogyakarta, and to reveal the effects of the pondok pesantren (specialfor the transgender people) in Notoyudan Pringgokusuman on their religious behaviorsin Yogyakarta.The research employed a descriptive quantitative method. The informantswere selected purposively. They were the founder of the pondok pesantren, transgendermembers of the pondok pesantren, and ustadz who often conducted Koranrecitations in Al-Fatah Pondok Pesantren, Yogyakarta. The data were collected throughinterviews, observations, literature studies, and documentation. The research instrumentwas the researchers themselves by using interview and observation guides. Thedata validity was obtained through triangulation. The data analysis technique was aqualitative one consisting of data reduction, data display, conclusion, and verification.The findings showed that the effects of AlFatah Pondok Pesantren were that itprovided a space for the transgender people to worship and to learn Islam as efforts toimrove the quality of their life. The religious activities were conducted on Mondayand Thursday. In sptite of that, Al-Fatah Pondok Pesantren did not give great impactsto their religious behaviours as those transgender people did not pray regularly andcarry out other religious activities.